Attitudes and Interest of YARSI Medical Clerkships Students toward Family Medicine - Wijayanti, Erlina; Susilowati, RW; Mahardhika, Zwasta Pribadi; Widianti, Dini; Yusnita, Yusnita; Mardhiyah, Dian (Faculty of Medicine, Public Health, and Nursing, 2023)
Background. Family medicine is a new specialty, so it is necessary to know the interests of students. Objectives. To find out the perception and interest of clerk students toward family physician careers. Methods. This research was a cross-sectional study at the Faculty of Medicine YARSI. Consecutive sampling in the period January to April 2023. Data was collected through online questionnaires. The analysis carried out includes univariate, bivariate, and multivariate analysis. Results. The sample involved 103 people. Students interested in becoming family physicians amounted to 46 people (44.7%). Individual characteristics are not significantly related. The determinant of student interest was the perception that family physician’s practice was attractive (p = 0.036; OR= 2.518 (95% CI= 1.060-5.981)). Conclusions. Family physicians play an important role in solving health problems in primary care. Intensification of learning about family medicine and primary care is needed to increase student interest.